An Evaluation of Speaking Materials in Think Globally Act Locally Textbook for Ninth Grade of Junior High School - Dwi Eka Putri; Arasuli Arasuli; Erni Sukesi (Journal of English Education and Teaching, 2022)
This research was intended to observe, evaluate, and discover the quality of the speaking materials which appear in Think Globally Act Locally textbook for ninth grade of junior high school published by the Ministry of Education and Culture 2018 revised edition. Researchers evaluated the speaking materials by using the Scott’s theory of good speaking materials. It was conducted by using descriptive qualitative research design. The research object was Think Globally Act Locally textbook, specifically the whole speaking materials on that book. The instruments consisted of evaluation table, documentation, and interview. The data were collected through six necessary steps, included (1) read the textbook thoroughly, (2) find out all the speaking materials, (3) observe all the speaking materials that was found, (4) identify the speaking materials regarding to the four criteria, (5) report the data through evaluation table, and (6) present the data in detail. The result of this study showed that there were 40 speaking materials found in the textbook, 30 of them filled the category of “good”, and 10 others reached the category of “sufficient”. In conclusion, overall the speaking materials in this textbook were classified as good. Therefore, researchers recommend this textbook to be implemented as the main source for speaking activities in classroom interaction.